If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (176 + -1y) = (115 + x) Remove parenthesis around (176 + -1y) 176 + -1y = (115 + x) Remove parenthesis around (115 + x) 176 + -1y = 115 + x Solving 176 + -1y = 115 + x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-176' to each side of the equation. 176 + -176 + -1y = 115 + -176 + x Combine like terms: 176 + -176 = 0 0 + -1y = 115 + -176 + x -1y = 115 + -176 + x Combine like terms: 115 + -176 = -61 -1y = -61 + x Divide each side by '-1'. y = 61 + -1x Simplifying y = 61 + -1x
| 5n-n+5=13 | | 4x^2+y^2+2y=0 | | -3=m-3 | | 3=l-5 | | 4n-2n+10=22 | | -9+y=7 | | f(x)=x^2+9x-1 | | 1.05t+0.63=-0.07t | | 4x+2(8)=4x(9) | | 10n+2=22 | | 13-6b=3+11b | | 9n+18=36 | | (99+x)=(176+y) | | -9(x+3)+3x+6=5x+9 | | 6.75t+7=15.5t+14 | | 4568b-4=7 | | -v+2=3 | | 116=-4(-4y)-9(2y)+y | | (w*3-9)+(w+4)=(w*3-9)+(w+4) | | 2x+3y=5.13 | | 16+b^2+6b=0 | | 4y^6(y^2+9y+2)= | | 8n^2-3n-16=24 | | -10+3x=-4 | | X+y=y+x+200 | | 57=3v+3 | | 89-116=-4(-4y)-9(2y) | | 4x+6+6x=36 | | x+y+z=2000zxy | | (7x-4x)=y | | -5x-2=-2x-17 | | 0.5(2n-10)=22 |